PENINGKATAN GERAK LOKOMOTOR MELALUI KEGIATAN GERAK DASAR TARI BETAWI JALI-JALI PADA USIA 4-5 TAHUN DI TK ISLAM AL-HASANAH JAKARTA TIMUR - Husna, Alifatu; Karyadi, Agung Cahya (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2019)
This study aims to improve locomotor movement skills, which should be improved is walking, running, jumping / jumping. Through the basic movement activities of the Betawi Jali-Jali dance. With movements that move places. At the age of 4-5 years at Al-Hasanah Islamic Kindergarten, East Jakarta, 2019/2020 school year. This research is a classroom action research, which is conducted in 2 cycles. The subjects in this study were 17 children aged 4-5 years. Data collection techniques are carried out by observation and documentation. The research instrument used was an observation guide. The action of data analysis used quantitative descriptive. The results showed that there was an increase in the locomotor movement ability of children, namely in the initial conditions of 25.10%, increasing in cycle I to 55.01%, and in cycle II increasing by 71.50%.